2016
DOI: 10.4174/astr.2016.90.2.95
|View full text |Cite
|
Sign up to set email alerts
|

A new risk-scoring model for predicting 30-day mortality after repair of abdominal aortic aneurysms in the era of endovascular procedures

Abstract: PurposeTo propose a new, multivariable risk-scoring model for predicting 30-day mortality in individuals underwent repair of abdominal aortic aneurysms (AAA).MethodsFour hundred eighty-five consecutive patients who underwent AAA repair from January 2000 to December 2010 were included in the study. Univariate and multivariate analyses were performed to evaluate the risk factors, and a risk-scoring model was developed.ResultsMultivariate analysis identified three independent preoperative risk factors associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…Renal complications and myocardial infarction, commonly presenting perioperatively, may have contributed to the higher perioperative mortality rate seen in the OSR cohort. This is in agreement with recent studies that demonstrated postoperative renal complications and MI to independently predict perioperative mortality following successful AAA repair [25].…”
Section: Postoperative Complicationssupporting
confidence: 93%
“…Renal complications and myocardial infarction, commonly presenting perioperatively, may have contributed to the higher perioperative mortality rate seen in the OSR cohort. This is in agreement with recent studies that demonstrated postoperative renal complications and MI to independently predict perioperative mortality following successful AAA repair [25].…”
Section: Postoperative Complicationssupporting
confidence: 93%
“…NICE guidelines (2008) state that 20% of 5 cm vessels and 25% of 6 cm vessels will rupture every year. However the surgery is also high risk and results in 5% mortality for open surgery and 1–2% for endovascular repair (Kim et al 2016). A pharmaceutical therapy to either reverse or retard aneurysm progression could prevent aneurysms from rupturing as well as the need for surgery, saving both lives and healthcare resources.…”
Section: Introductionmentioning
confidence: 99%